ChemInform Abstract: Marine Natural Products. Issue 23 (May 2016) - Blunt, John W.; Copp, Brent R.; Keyzers, Robert A.; Munro, Murray H. G.; Prinsep, Michele R.
Abstract: Review: isolation, biological activities, source organisms, biosynthetic studies, and irst syntheses of marine natural products published in 2014; 938 refs.